2009
DOI: 10.1348/000709908x368848
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationships between trait emotional intelligence and objective socio‐emotional outcomes in childhood

Abstract: Trait EI is successfully operationalized through the TEIQue-CF and has important and multifaceted implications for the socialization of primary schoolchildren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
128
2
38

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(188 citation statements)
references
References 57 publications
(79 reference statements)
20
128
2
38
Order By: Relevance
“…The most likely reason for the results is because the strength of the relationship between emotional intelligence, social adjustment and academic adjustment is higher for students possessing higher critical thinking. The present study's findings support that of Mavroveli et al's (2009) contention that moderator variable may impact the relationship between emotional intelligence and academic success at university. Hence, according to the finding of this study, students with high critical thinking lead to stronger/significant relationship between emotional intelligence, and social and academic adjustment.…”
Section: Discussionsupporting
confidence: 88%
“…The most likely reason for the results is because the strength of the relationship between emotional intelligence, social adjustment and academic adjustment is higher for students possessing higher critical thinking. The present study's findings support that of Mavroveli et al's (2009) contention that moderator variable may impact the relationship between emotional intelligence and academic success at university. Hence, according to the finding of this study, students with high critical thinking lead to stronger/significant relationship between emotional intelligence, and social and academic adjustment.…”
Section: Discussionsupporting
confidence: 88%
“…Within educational settings, trait EI has been shown to relate to adaptive behaviors, such as higher attendance, and positive peer relations (Gugliandolo, et al, 2015;Ruttledge & Petrides, 2012;Mavroveli, Petrides, Sangareau & Furnham, 2009;Mavroveli, Petrides, Shove & Whitehead, 2008;Mavroveli, Petrides, Rieffe, & Bakker, 2007;Petrides, Sangareau, Furnham & Frederickson, 2006;Santeso, Reker, Schmidt & Segalowitz, 2006). Empirical evidence has also shown that trait EI has a positive effect on happiness, life satisfaction, affect (Platsidou, 2013;Chamorro-Premuzic, Furnham & Lewis, 2007;Petrides & Furnham, 2003), and academic success, primarily among at risk students (Mavroveli, Sanchez-Ruiz, 2010;Parker, Summerfeldt, Hogan & Majeski, 2004;.…”
Section: Trait Emotional Intelligence (Ei) and Educational Outcomesmentioning
confidence: 99%
“…Response coherence has shown to be correlated with social connectedness (Mauss et al 2011). A study by Freudenthaler et al (2012) showed that the coherence between different emotional response systems co-varied positively with trait emotional self-efficacy, which is a powerful predictor of social functioning (e.g., Mavroveli et al 2009). In addition, individuals with ASD were found to score lower on trait emotional self-efficacy than controls (Petrides et al 2011).…”
Section: Humorous Film Clipsmentioning
confidence: 99%